2009
DOI: 10.1161/atvbaha.108.177105
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Apolipoprotein F Reduces HDL Cholesterol Levels In Vivo

Abstract: Objective— Apolipoprotein F (ApoF) is a protein component of several lipoprotein classes including HDL. It is also known as lipid transfer inhibitor protein (LTIP) based on its ability to inhibit lipid transfer between lipoproteins ex vivo. We sought to investigate the role of ApoF in HDL metabolism. Methods and Results— Adeno-associated viruses (AAV) based on serotype 8, were used to overexpress either murine or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 21 publications
4
53
0
Order By: Relevance
“…The HDL3c proteome also contains apoA-I; apoA-II; apoD; apoM; SAA 1, 2, and 4; apoC-I; apoC-II; and apoE (Davidson et al 2009). Consistent with these data, apoL-I (Hajduk et al 1989), apoF (He et al 2008;Lagor et al 2009), apoJ (de Silva et al 1990a, b;Bergmeier et al 2004), PON1 (Kontush et al 2003;Bergmeier et al 2004), apoA-IV (Bisgaier et al 1985;Ohta et al 1985), apoM (Wolfrum et al 2005), apoD (Campos and McConathy 1986) and SAA1/ 2 (Benditt and Eriksen 1977;Coetzee et al 1986) are known to preferentially co-isolate with dense HDL3. Furthermore, small, dense HDL may also represent a preferential carrier for human CETP (Marcel et al 1990).…”
Section: Heterogeneity In Hdl Proteinsmentioning
confidence: 81%
See 1 more Smart Citation
“…The HDL3c proteome also contains apoA-I; apoA-II; apoD; apoM; SAA 1, 2, and 4; apoC-I; apoC-II; and apoE (Davidson et al 2009). Consistent with these data, apoL-I (Hajduk et al 1989), apoF (He et al 2008;Lagor et al 2009), apoJ (de Silva et al 1990a, b;Bergmeier et al 2004), PON1 (Kontush et al 2003;Bergmeier et al 2004), apoA-IV (Bisgaier et al 1985;Ohta et al 1985), apoM (Wolfrum et al 2005), apoD (Campos and McConathy 1986) and SAA1/ 2 (Benditt and Eriksen 1977;Coetzee et al 1986) are known to preferentially co-isolate with dense HDL3. Furthermore, small, dense HDL may also represent a preferential carrier for human CETP (Marcel et al 1990).…”
Section: Heterogeneity In Hdl Proteinsmentioning
confidence: 81%
“…ApoF is synthesised in the liver and heavily glycosylated with both O-and N-linked sugar groups. Such glycosylation renders the protein highly acidic and results in a molecular mass some 40 % greater than predicted (Lagor et al 2009).…”
Section: Apolipoproteinsmentioning
confidence: 93%
“…Apo F bound to LDL has LTIP activity, whereas the HDL-associated apo F exists as part of the 470 kDa inactive complex. Although human apo F preferred to associate with the larger HDL particles in the gel filtration profile, apo F-containing particles show density in the HDL3 range 7,8) . By immunoblotting analysis, plasma apo F associated with LDL was markedly higher in hypercholesterolemic subjects than in normolipidemic subjects, which was due to the distribution of apo F and its lipoprotein composition 11,12) .…”
Section: Cloning Of Human Apo F and Expression Of Recombinant Human Amentioning
confidence: 96%
“…Apolipoprotein F (apo F) is a 29-kDa acidic gly-coprotein associated with LDL 1, 2) and HDL 3-5) in human and mouse plasma [6][7][8] . It is also known as a lipid transfer inhibitor protein (LITP) for its ability to inhibit lipid transfer among lipoproteins in vitro 1) .…”
Section: Introductionmentioning
confidence: 99%
“…Plasma apoF levels were found to be positively associated with HDL cholesterol in males but not in females (Morton et al 2008). The Rader group subsequently showed that overexpression of apoF in mice reduced HDL cholesterol levels by accelerating clearance from the circulation (Lagor et al 2009). A later study showed that a murine apoF knockout model had no substantial effect on plasma lipid concentrations, HDL size, lipid, or protein (Lagor et al 2012) although a reduced ability to promote cholesterol efflux was observed.…”
Section: Apolipoprotein Fmentioning
confidence: 99%